2016
DOI: 10.1371/journal.pone.0162510
|View full text |Cite
|
Sign up to set email alerts
|

The German Version of the Dutch Eating Behavior Questionnaire: Psychometric Properties, Measurement Invariance, and Population-Based Norms

Abstract: The Dutch Eating Behavior Questionnaire is an internationally widely used instrument assessing different eating styles that may contribute to weight gain and overweight: emotional eating, external eating, and restraint. This study aimed to evaluate the psychometric properties of the 30-item German version of the DEBQ including its measurement invariance across gender, age, and BMI-status in a representative German population sample. Furthermore, we examined the distribution of eating styles in the general popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 39 publications
8
80
1
2
Order By: Relevance
“…health concerns, price and convenience orientation) (55) , has been found to be invariant across European samples (56) . Also a long tradition of research on the Dutch Eating Behavior Questionnaire (57) showed that its factors (emotional, restrained and external eating) are valid across a large range of European and Asian samples (58)(59)(60) . It is, however, important to note that the scale Need and Hunger did not appear as a reliable scale in all countries.…”
Section: Discussionmentioning
confidence: 99%
“…health concerns, price and convenience orientation) (55) , has been found to be invariant across European samples (56) . Also a long tradition of research on the Dutch Eating Behavior Questionnaire (57) showed that its factors (emotional, restrained and external eating) are valid across a large range of European and Asian samples (58)(59)(60) . It is, however, important to note that the scale Need and Hunger did not appear as a reliable scale in all countries.…”
Section: Discussionmentioning
confidence: 99%
“…The final data set included 2,513 individuals. Full details of this survey have been previously published ().…”
Section: Methodsmentioning
confidence: 99%
“…Mean subscale scores were computed, with higher scores indicating more frequent nonnormative eating behavior. The German version of the DEBQ has shown good validity and adequate reliability (). Cronbach alphas in the GWCR sample were 0.82 for restraint, 0.94 for emotional eating, and 0.89 for external eating; in the GP sample, the respective values were 0.92, 0.94, and 0.89.…”
Section: Methodsmentioning
confidence: 99%
“…Studien, die Messinstrumente in der deutschen Allgemeinbevölkerung validieren, erbrachten geschlechts-und altersspezifische sowie BMI-spezifische Normwerte für dieses Instrument. Sowohl mit dem DEBQ als auch dem TFEQ ließen sich Unterschiede im restriktiven Essverhalten zwischen BMI-Gruppen zeigen, wobei ein höherer BMI mit einer höheren Ausprägung des restriktiven Essverhaltens einherging [58,59]. Einige Studien zeigten einen negativen Zusammenhang zwischen BMI und restriktivem Essverhalten [25,60].…”
Section: Wirkungsmechanismen Des Restriktiven Essverhaltensunclassified